PENGARUH PEMBERIAN REWARD AND PUNISHMENT TERHADAP PENINGKATAN MOTIVASI BELAJAR PENDIDIKAN JASMANI PESERTA DIDIK ( STUDI PADA SISWA KELAS VIII SMP NEGERI 1 BAURENO ) - PERDANA KUSUMA, VREDI (Jurnal Pendidikan Olahraga dan Kesehatan, 2013)
Abstract Learning is a change in behavior due to experience of having experienced living beings, an educator must be able to turn the atmosphere so that the learning activities effective and fun. One way to liven up the atmosphere that is the provision of reward and punishment to the appreciation is expected students more active in participating in learning activities. The purpose of this study is to find empirical evidence of whether the provision of reward and punishment can increase motivation students' at class VIII SMP Negeri 1 Baureno, increased motivation to learn at class VIII SMP Negeri 1 Baureno given to physical education. In this study using a purposive sample, purposive sample is done by taking the subject is not based on the strata, or a random area but based on the existence of a particular purpose. In this research uses type of research experiments, research experimentation is an research with doing activities of experiments who aims know the symptoms or influence that arise as the existence of such experiments are. The population was overall eighth grade students of SMP Negeri 1 Baureno with data retrieval by using a questionnaire to collect data. Based on the results of the study the percentage increase in the experimental group was 3.576% and in the control group was 2.690% difference between the post-test experimental group and a control group of 0.83 larger experimental group. From all the results and the value appears, it concluded there was no significant effect of the effect of reward and punishment to the increased motivation for learning physical education 1,054 t <t table 2.010.  Keywords: motivation, physical education, reward and punishment.